RADIOFREQUENCY DENERVATION OF PULMONARY ARTERY IN SURGERY OF DYSPLASTIC MITRAL VALVE DEFECTS WITH SEVERE PULMONARY HYPERTENSION - S. I. Zheleznev; D. P. Demidov; A. V. Afanasiev; V. M. Nazarov; I. I. Demin; A. V. Bogachev-Prokofiev; D. A. Astapov; A. M. Karaskov (Российский кардиологический журнал)
Pulmonary hypertension is an increase of pulmonary artery mean pressure for more than 25 mmHg at rest, measured by direct tensometry, and it includes a broad spectrum of diseases. Mechanisms of pulmonary hypertension are a connection of diverse vicious circles determining chronic progression of the disease, progradient worsening of patient’s condition and serious decline in life quality, and premature death. Severe pulmonary hypertension significantly raises risk of perioperation mortality and closely correlates with long-term survival. We propose an original technics of pulmonary artery denervation during one-stage cardiosurgical interventions, that confirmed its safety. Radiofrequency ablation of pulmonary artery in patients with dysplasia of connective tissue and high combined (precapillary and postcapillary) pulmonary hypertension, undergoing surgery for severe sympthomatic mitral insufficiency, is an effective procedure. An assessment is needed for short- and long-term results. Further studies will make it to know, whether the achieved hemodynamical benefits do turn to better clinical outcomes.